A Systematic Review of Library Services Provision in Response to COVID-19 Pandemic - Ayeni, Philips O.; Agbaje, Blessed O.; Tippler, Maria (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2021)
Objective – Libraries have had to temporarily shut their doors because of the COVID-19 pandemic, resulting in the provision of online and remote services. This review analyzed services offered by libraries, the technological tools used, and the challenges facing libraries during the pandemic. Methods – This study employed a systematic literature review, following the PRISMA checklist (Moher at al., 2009). The Building Blocks search strategy was employed to search for keywords of concepts in Library and Information Science Abstract (LISA), Library and Information Science Technology Abstract (LISTA), Library Science Database, Web of Science (WoS) core collections, and Google Scholar. A set of inclusion and exclusion criteria was pre-determined by the authors prior to database searching. Quality assessment of included studies was performed using the Mixed Methods Appraisal Tool (Hong et al., 2018). A tabular approach was used to provide a summary of each article allowing the synthesis of results, which led to the identification of eight broad categories of services provided by libraries in included studies. Results – The first set of searches from the 5 databases produced 3,499 results. After we removed duplicates and applied the inclusion and exclusion criteria based on titles and abstracts, 37 potentially relevant articles were identified. Further screening of the full-text led to the final inclusion of 23 articles used for the qualitative synthesis. The majority of the studies were conducted in the United States of America (n= 6, 26.1%), followed by India (n=4, 17%), and China (n=2, 8.7%). The remaining studies were carried out in United Kingdom, Ireland, Canada, Mexico, Romania, Czech Republic, Indonesia, Pakistan, Nigeria, Lesotho, and Zimbabwe. The most common method used in selected studies was the case study (n= 11, 48%), followed by survey (n=7, 30.4%), content analysis (n=4, 17.4%), and mixed methods (n=1, 4.3%). The majority of the studies were carried out in academic libraries (74%), while the rest were based on medical, public, and special libraries. Findings show that the majority of academic libraries in the included studies are providing and expanding access to electronic resources (n=16, 69.6%) and increasing open access resources and services (n=11, 47.8%). More so, most academic libraries are assisting in virtual education and teaching endeavors of faculty and students (n=13, 56.5%). In addition, some medical and public libraries are bolstering public health safety through health literacy (n=12, 52.2%), supporting research efforts, and engaging in virtual reference services, among others. In order to carry out these services, libraries are harnessing several educational, social networking, communication, and makerspaces technologies. Most of the libraries in the included studies reported budgetary challenges, and the need for new ICT infrastructure and Internet service as they move their services online. Conclusion – This review found that libraries are adapting in a number of ways to continue their roles in meeting patrons’ needs in spite of the growing challenges posed by COVID-19 restrictions and lockdown. For libraries to thrive in these trying times, there must be a well-structured approach to ensuring continuity of services. Libraries should prioritize the acquisition of electronic resources as well as increase their efforts to digitize resources that are only available in printed copies. As library services have predominantly shifted online, there should be concerted effort and support from government and funding agencies to equip libraries with the technological facilities needed to provide cutting-edge services. The quality assessment of the included studies shows that there is need for rigor and transparency in the methodological description of studies investigating library services provision in a pandemic. This review provides an overview of the ways libraries have responded to the challenges posed by a global pandemic, and hence will be of use and interest to all librarians especially those in health and academic sectors.